Lithium ion battery, positive electrode active material and electric equipment
By using slender primary particles in the positive electrode active material of lithium-ion batteries, the problem of stress accumulation during the battery cycle is solved, and better electrode stability and cycling performance are achieved.
Patent Information
- Application Number
- CN202411730352.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-28
- Publication Date
- 2025-04-15
AI Technical Summary
During the circulation process of lithium-ion batteries, the particles of the positive electrode material accumulate, resulting in reduced stability of the electrode sheet and deterioration of circulation performance.
A positive electrode active material containing slender primary particles is used. The particle size range of the slender primary particles is 0.1μm≤P2≤0.6μm and 0.1μm
Through the arrangement of slender primary particles, the stress concentration inside the secondary particles is reduced, stress release is improved, the side reaction between the positive electrode particles and the electrolyte is reduced, and the circulation performance of lithium-ion batteries is improved.
Smart Images

Figure CN119833712A_ABST
Abstract
Description
Technical Field
[0001] The present application relates to the technical field of lithium batteries, and in particular to a lithium ion battery, a positive electrode active material and an electrical device. Background Art
[0002] In recent years, lithium-ion batteries have made great progress. Lithium-ion batteries can be widely used in energy storage power systems such as hydropower, thermal power, wind power and solar power stations, as well as electric vehicles, power tools, military equipment, aerospace and other fields.
[0003] Among them, during the cycle of lithium-ion batteries, there is a problem of stress accumulation in the positive electrode material particles, which leads to reduced stability of the positive electrode plate, increased side reactions of the lithium-ion secondary battery, and deteriorated cycle performance. The above statements are only used to provide background technical information related to this application and do not necessarily constitute prior art. Summary of the invention
[0004] In view of this, the main technical problem to be solved by the present application is the problem of deterioration of battery cycle performance caused by stress accumulation of positive electrode material particles, thereby providing a lithium-ion battery, positive electrode active material and electrical equipment, which can improve the reduced stability of the positive electrode sheet caused by stress accumulation of positive electrode material particles, and help improve the cycle performance of lithium-ion batteries.
[0005] The first aspect of the present application provides a lithium-ion battery, which includes a shell, a battery cell assembly and an electrolyte arranged in the shell, the battery cell assembly is located in the electrolyte, the battery cell assembly includes a positive electrode sheet, a negative electrode sheet and a separator, the separator is located between the positive electrode sheet and the negative electrode sheet, the positive electrode sheet includes a positive electrode collector and a positive electrode film layer arranged on at least one side of the positive electrode collector, the positive electrode film layer includes a positive electrode active material, the positive electrode active material includes lithium nickel cobalt manganese oxide, and the molar proportion of nickel in other metal elements other than lithium is greater than or equal to 85%; the positive electrode active material includes secondary particles, the secondary particles include primary particles, the primary particles include slender primary particles, the particle size of each slender primary particle includes a longest diameter P1 and a shortest diameter P2, 1.5≤P1 / P2≤10, 0.1μm<P1≤3.5μm, 0.1μm≤P2≤0.6μm; the slender primary particles are arranged radially.
[0006] By setting 1.5≤P1 / P2≤10, 0.1μm<P1≤3.5μm, 0.1μm≤P2≤0.6μm, the primary particles are slender primary particles, and the slender primary particles are arranged radially. When the volume of the primary particles changes during the charging and discharging process of the battery, the slender primary particles can be intertwined with each other, and the degree of mutual squeezing between the slender primary particles is relatively small, which is beneficial to alleviate the stress concentration caused by the volume change. At the same time, the radially arranged slender primary particles can expand and contract more evenly during the charging and discharging cycle, so that they have higher adaptability to deformation and can better transfer stress when deformation occurs; therefore, the stress concentration inside the secondary particles is low, and stress release is improved, thereby effectively alleviating the cracking inside the secondary particles, reducing the side reaction between the positive electrode particles and the electrolyte, and is beneficial to improving the cycle performance of the lithium-ion battery.
[0007] In one embodiment, based on the total number of primary particles in a single secondary particle, the number of slender primary particles accounts for 60% to 85%. At this time, most of the primary particles in the secondary particles are slender primary particles, so the order of the primary particle arrangement can be improved, the stress concentration between the primary particles can be further reduced, and stress release can be more easily performed.
[0008] In one embodiment, based on the total number of primary particles in a single secondary particle, the number of slender primary particles accounts for 70% to 85%. When the number of slender primary particles is within the above range, the order of the primary particle arrangement can be further improved, the stress concentration between the primary particles can be reduced, and stress release can be performed more easily.
[0009] In one embodiment, in a cross-sectional scanning electron microscope image of a secondary particle passing through the geometric center of the particle, the cross section of a single secondary particle includes N1 primary particles; 250≤N1≤450. The cross section of a single secondary particle includes the above number of primary particles, and the number of primary particles contained in secondary particles of the same size is relatively appropriate. During the battery cell cycle, the lithium ion intercalation performance is better, the stress release is easier, which is beneficial to reduce the internal stress concentration, and is beneficial to improve the charge and discharge efficiency and cycle stability of the battery; at the same time, there are fewer crystal faces in contact with the electrolyte, fewer side reactions, and better electrochemical performance.
[0010] In one embodiment, the secondary particles are spherical in shape. The elongated primary particles are arranged radially so that the secondary particles are spherical in shape, and the secondary particles are less likely to crack.
[0011] In one embodiment, the volume median particle size Dv50 of the secondary particles is 8.5 μm to 12 μm. When the volume median particle size Dv50 of the secondary particles is within the above range, the contact area with the electrolyte is small, which is beneficial to reduce the side reactions of the positive electrode active material, thereby improving the cycle performance of the lithium ion battery; at the same time, the diffusion of active lithium ions in the positive electrode active material is also relatively easy, thereby taking into account the rate performance of the lithium ion battery.
[0012] In one embodiment, the positive electrode active material includes a structural formula of Li a Ni b Co c Mn d M1 e O f The material, wherein the M1 element includes one or more of Na, Mg, Zr, Al, Ca, W, Nb, Ta, Sr, K, Sb, Mo, W, 0.5≤a≤1.2, 0.85≤b≤0.99, 0<c≤0.1, 0<d≤0.05, 1.9≤f≤2.2, b+c+d+e=1. The positive electrode active material of the above structural formula has a higher energy density and better stability.
[0013] In one embodiment, a first coating layer is formed on the surface of the positive electrode active material, and the first coating layer includes a first element, and the first element includes one or more of Co, Al, F, and Ti. The first element is beneficial to improving the surface and interface stability of the positive electrode active material, thereby improving the electrochemical performance of the positive electrode active material.
[0014] In one embodiment, based on the molar amount of the positive electrode active material, the content of Co is 7000ppm to 15000ppm; and / or based on the molar amount of the positive electrode active material, the content of Al is 300ppm to 1000ppm; and / or based on the molar amount of the positive electrode active material, the content of F is 0 to 750ppm; and / or based on the molar amount of the positive electrode active material, the content of Ti is 300ppm to 1000ppm. Within the above range, the first element can better improve the interface stability and electrochemical performance of the positive electrode active material.
[0015] In one embodiment, a second coating layer is formed on the surface of the positive electrode active material, and the second coating layer includes a second element, and the second element includes one or more of B, Al, and Y. The second element is beneficial to reduce the surface activity of the positive electrode active material, improve the surface stability of the positive electrode active material, and reduce the side reaction between the positive electrode active material and the electrolyte.
[0016] In one embodiment, based on the molar amount of the positive electrode active material, the content of the second element is 500 ppm to 3000 ppm. Within the above range, the second element can better improve the surface stability and electrochemical performance of the positive electrode active material.
[0017] The second aspect of the present application also provides a positive electrode active material, the positive electrode active material includes lithium nickel cobalt manganese oxide, the molar proportion of nickel element in other metal elements except lithium element is greater than or equal to 85%; the positive electrode active material includes secondary particles, the secondary particles include primary particles, the primary particles include slender primary particles, the particle size of each slender primary particle includes a longest diameter P1 and a shortest diameter P2, 1.5≤P1 / P2≤10, 0.1μm<P1≤3.5μm, 0.1μm≤P2≤0.6μm; the slender primary particles are arranged radially. By setting 1.5≤P1 / P2≤10, 0.1μm<P1≤3.5μm, 0.1μm≤P2≤0.6μm, the primary particles are slender primary particles, and the slender primary particles are arranged radially. When the volume of the primary particles changes during the charging and discharging process of the battery, the slender primary particles can be intertwined with each other, and the degree of mutual squeezing between the slender primary particles is relatively small, which is beneficial to alleviate the stress concentration caused by the volume change. At the same time, the radially arranged slender primary particles can expand and contract more evenly during the charging and discharging cycle, so that they have higher adaptability to deformation and can better transfer stress when deformation occurs; therefore, the stress concentration inside the secondary particles is low, and stress release is improved, thereby effectively alleviating the cracking inside the secondary particles, reducing the side reaction between the positive electrode particles and the electrolyte, and is beneficial to improving the cycle performance of the lithium-ion battery.
[0018] In one embodiment, based on the total number of primary particles in a single secondary particle, the number of slender primary particles accounts for 60% to 85%. At this time, most of the primary particles in the secondary particles are slender primary particles, so the order of the primary particle arrangement can be improved, the stress concentration between the primary particles can be further reduced, and stress release can be more easily performed.
[0019] The third aspect of the present application also provides an electrical device, comprising the lithium ion battery of the first aspect of the present application and / or the positive electrode active material of the second aspect of the present application. Since the electrical device of the present application comprises the lithium ion battery and / or the positive electrode active material provided by the present application, it has at least the same advantages as the lithium ion battery.
[0020] The above description is only an overview of the technical solution of the present application. In order to more clearly understand the technical means of the present application, it can be implemented in accordance with the contents of the specification. In order to make the above and other purposes, features and advantages of the present application more obvious and easy to understand, the specific implementation methods of the present application are listed below. BRIEF DESCRIPTION OF THE DRAWINGS
[0021] Figure 1 is a scanning electron microscope (SEM) photograph of a positive electrode active material particle according to an embodiment of the present application;
[0022] Figure 2 It is a schematic flow chart of a method for preparing a positive electrode active material provided by the first embodiment of the present application;
[0023] Figure 3 is a schematic flow chart of step S110 in the method for preparing a positive electrode active material provided in the first embodiment of the present application;
[0024] Figure 4 is a schematic flow chart of a method for preparing a positive electrode active material provided in a second embodiment of the present application;
[0025] Figure 5 is a schematic flow chart of a method for preparing a positive electrode active material provided in a third embodiment of the present application;
[0026] Figure 6 is a schematic structural diagram of a lithium-ion battery according to one embodiment of the present application;
[0027] Figure 7 is a schematic diagram of the exploded structure of a battery according to one embodiment of the present application;
[0028] Figure 8a It is a partial structural schematic diagram of an electrical device according to an embodiment of the present application;
[0029] Figure 8b It is a schematic diagram of an electrical device according to one embodiment of the present application. DETAILED DESCRIPTION
[0030] Hereinafter, the embodiments of the lithium-ion battery, battery, and electrical equipment of the present application are specifically disclosed in detail with appropriate reference to the accompanying drawings. However, there may be cases where unnecessary detailed descriptions are omitted. For example, there are cases where detailed descriptions of well-known matters and repeated descriptions of actually the same structures are omitted. This is to avoid the following description from becoming unnecessarily lengthy and to facilitate the understanding of those skilled in the art. In addition, the drawings and the following description are provided for those skilled in the art to fully understand the present application and are not intended to limit the subject matter described in the claims.
[0031] The "range" disclosed in the present application is defined in the form of a lower limit and an upper limit, and a given range is defined by selecting a lower limit and an upper limit, and the selected lower limit and upper limit define the boundaries of the particular range. The range defined in this way can be inclusive or exclusive of the end values, and can be arbitrarily combined, that is, any lower limit can be combined with any upper limit to form a range. For example, if a range of 60 to 120 and 80 to 110 is listed for a particular parameter, it is understood that a range of 60 to 110 and 80 to 120 is also expected. In addition, if the minimum range values 1 and 2 are listed, and if the maximum range values 3, 4 and 5 are listed, the following ranges can all be expected: 1 to 3, 1 to 4, 1 to 5, 2 to 3, 2 to 4 and 2 to 5. In the present application, unless otherwise specified, the numerical range "a to b" represents an abbreviation of any real number combination between a and b, where a and b are both real numbers. For example, the numerical range "0-5" means that all real numbers between "0-5" are listed in this document, and "0-5" is just an abbreviation of these numerical combinations. In addition, when a parameter is expressed as an integer ≥ 2, it is equivalent to disclosing that the parameter is, for example, an integer of 2, 3, 4, 5, 6, 7, 8, 9, 10, 11, 12, etc.
[0032] Unless otherwise specified, all embodiments and optional embodiments of the present application can be combined with each other to form a new technical solution.
[0033] Unless otherwise specified, all technical features and optional technical features of this application can be combined with each other to form a new technical solution.
[0034] Unless otherwise specified, all steps of the present application may be performed sequentially or randomly, preferably sequentially. For example, a method includes steps (a) and (b), which means that the method may include steps (a) and (b) performed sequentially, or may include steps (b) and (a) performed sequentially. For example, a method may also include step (c), which means that step (c) may be added to the method in any order, for example, the method may include steps (a), (b) and (c), or may include steps (a), (c) and (b), or may include steps (c), (a) and (b), etc.
[0035] If there is no special explanation, the "include" and "comprising" mentioned in this application represent open-ended or closed-ended expressions. For example, "include" and "comprising" may represent that other components not listed may also be included or only listed components may be included or only listed components may be included.
[0036] If not specifically stated, in this application, the term "or" is inclusive. For example, the phrase "A or B" means "A, B, or both A and B". More specifically, any of the following conditions satisfies the condition "A or B": A is true (or exists) and B is false (or does not exist); A is false (or does not exist) and B is true (or exists); or both A and B are true (or exist).
[0037] During the charge and discharge process of lithium-ion batteries, active lithium ions are embedded and extracted from the positive electrode material, causing the expansion and contraction of the lattice, thereby generating stress accumulation inside the material particles. This stress accumulation may lead to the formation of microcracks inside the material particles, which in turn affects the cycle stability and safety of the battery.
[0038] Based on this, the present application proposes a lithium-ion battery, which includes a shell, a battery cell assembly and an electrolyte disposed in the shell, the battery cell assembly is located in the electrolyte, the battery cell assembly includes a positive electrode sheet, a negative electrode sheet and a separator, the separator is located between the positive electrode sheet and the negative electrode sheet, the positive electrode sheet includes a positive current collector and a positive electrode film layer disposed on at least one side of the positive current collector, the positive electrode film layer includes a positive electrode active material, the positive electrode active material includes lithium nickel cobalt manganese oxide, and the molar proportion of nickel in other metal elements other than lithium is greater than or equal to 85%. Among them, the positive electrode active material includes secondary particles, the secondary particles include primary particles, the primary particles include slender primary particles, the particle size of each slender primary particle includes the longest diameter P1 and the shortest diameter P2, 1.5≤P1 / P2≤10, 0.1μm<P1≤3.5μm, 0.1μm≤P2≤0.6μm; the slender primary particles are arranged radially.
[0039] By setting 1.5≤P1 / P2≤10, 0.1μm<P1≤3.5μm, 0.1μm≤P2≤0.6μm, the primary particles are slender primary particles, and the slender primary particles are arranged radially. When the volume of the primary particles changes during the charging and discharging process of the battery, the slender primary particles can be intertwined with each other, and the degree of mutual squeezing between the slender primary particles is relatively small, which is beneficial to alleviate the stress concentration caused by the volume change. At the same time, the radially arranged slender primary particles can expand and contract more evenly during the charging and discharging cycle, so that they have higher adaptability to deformation and can better transfer stress when deformation occurs; therefore, the stress concentration inside the secondary particles is low, and stress release is improved, thereby effectively alleviating the cracking inside the secondary particles, reducing the side reaction between the positive electrode particles and the electrolyte, and is beneficial to improving the cycle performance of the lithium-ion battery.
[0040] See also Figure 1 , Figure 1 is a scanning electron microscope (SEM) photograph of the positive electrode active material particles according to one embodiment of the present application, such as Figure 1 As shown, the elongated primary particles in the secondary particles are arranged radially.
[0041] In the embodiment of the present application, the positive electrode active material of the lithium ion battery includes lithium nickel cobalt manganese oxide. Lithium nickel cobalt manganese oxide gathers the advantages of the three elements of nickel (Ni), cobalt (Co), and manganese (Mn) through the synergistic effect of elements, while maintaining the electrode material with high specific capacity and good stability, it also reduces the preparation cost. Among them, the molar proportion of nickel element in other metal elements except lithium element is greater than or equal to 85%, which can effectively improve the specific capacity of the positive electrode active material, thereby helping to improve the energy density of lithium ion batteries. The molar proportion of nickel element can be 85%, 88%, 90%, 95%, 99%, etc., or a range composed of any two of the above values, for example, it can be 85% to 88%, 85% to 90%, 90% to 95%, 95% to 99%, etc.
[0042] In the embodiment of the present application, the positive electrode active material includes secondary particles, and the secondary particles include primary particles, and the primary particles refer to the smallest unit generated directly by a physical or chemical process. Secondary particles are larger particles formed by cold pressing, sintering, agglomeration or other mechanical and physical processes of primary particles. In some embodiments, secondary particles can be larger aggregates or clusters formed by bonding multiple primary particles.
[0043] The primary particles include elongated primary particles, the longest diameter P1 of the elongated primary particles is defined as the longest dimension of the primary particles, the elongated primary particles have a maximum dimension along the first direction of the geometric center of the elongated primary particles, and the maximum dimension is the longest diameter P1. The shortest diameter P2 of the elongated primary particles is defined as the shortest dimension of the primary particles, the elongated primary particles have a minimum dimension along the second direction of the geometric center of the elongated primary particles, and the minimum dimension is the shortest diameter P2, wherein the first direction intersects with the second direction. In one embodiment, the first direction is perpendicular to the second direction. 1.5≤P1 / P2≤10, the longest diameter and the shortest diameter of the primary particles differ greatly, and the shape is elongated. P1 / P1 can be 1.5, 1.6, 2, 3, 4.8, 5, 6, 7, 9, 10, etc., or a range consisting of any two of the above values, for example, it can be 1.5-1.6, 2-4.8, 1.5-6, 5-7, 9-10, etc.
[0044] In the embodiment of the present application, 0.1 μm<P1≤3.5 μm, 0.1 μm≤P2≤0.6 μm.
[0045] P1 may be 0.1 μm, 0.15 μm, 0.2 μm, 0.3 μm, 0.35 μm, 0.5 μm, 1 μm, 1.5 μm, 2.2 μm, 2.8 μm, 3 μm, 3.5 μm, etc., or a range consisting of any two of the above values, for example, 0.1 μm to 0.5 μm, 0.15 μm to 0.35 μm, 1 μm to 1.5 μm, 2.2 μm to 2.8 μm, 3 μm to 3.5 μm, etc. P2 may be 0.1 μm, 0.3 μm, 0.4 μm, 0.45 μm, 0.5 μm, 0.55 μm, 0.6 μm, etc., or a range consisting of any two of the above values, for example, 0.3 μm to 0.4 μm, 0.45 μm to 0.5 μm, 0.55 μm to 0.6 μm, etc.
[0046] P1 and P2 can be characterized by scanning electron microscopy (SEM).
[0047] When P1 and P2 of the elongated primary particles are within the above range, the elongated primary particles have a larger specific surface area than the spherical primary particles, and have more surfaces that can contact the electrolyte. The diffusion distance of lithium ions in the elongated primary particles is relatively short, which is beneficial to improving the transmission performance of lithium ions, so that lithium ions can be embedded and extracted relatively quickly and evenly inside the positive electrode material, and the volume change of the positive electrode material during the charge and discharge process is relatively stable. When the longest diameter P1 of the elongated primary particles is less than 3.5μm, the diffusion path of lithium ions is shorter and the diffusion resistance is smaller, which is beneficial to improving the lithium ion transmission performance; when P1 is greater than 0.1μm, the preparation process of the positive electrode active material is less difficult and has fewer side reactions. The effect of the shortest diameter P2 of the elongated primary particles on the lithium ion diffusion performance is the same as above. At the same time, based on the value range of P1, the value range of P2 enables the value of P1 / P2 to meet the requirements of the elongated primary particles.
[0048] In one embodiment, 0.3 μm≤P1≤3.5 μm, and 0.1 μm≤P2≤0.6 μm. In this case, the difficulty of preparing the positive electrode active material can be further reduced.
[0049] In one embodiment, the molar proportion of nickel in the metal elements other than lithium is greater than or equal to 90%, and can be 90%, 92%, 95%, 98%, 99%, etc., or a range consisting of any two of the above values, for example, it can be 90% to 92%, 95% to 98%, 98% to 99%, etc., which is beneficial to further improve the specific capacity of the positive electrode active material and the energy density of the lithium-ion battery.
[0050] In the embodiment of the present application, based on the total number of primary particles in a single secondary particle, the number of elongated primary particles accounts for 60% to 85%. For example, it can be 60%, 62%, 65%, 73%, 77%, 85%, etc., or a range consisting of any two of the above values, for example, it can be 60% to 62%, 65% to 73%, 77% to 85%, etc.
[0051] At this time, most of the primary particles in the secondary particles are slender primary particles, which can improve the orderliness of the primary particle arrangement, further reduce the stress concentration between the primary particles, make it easier to release stress, effectively alleviate the cracking inside the secondary particles, reduce the occurrence of cracks in the positive electrode sheet, and improve the stability of the positive electrode sheet, which is beneficial to improving the cycle performance of lithium-ion batteries.
[0052] In the embodiment of the present application, based on the total number of primary particles in a single secondary particle, the number of elongated primary particles accounts for 70% to 85%. For example, it can be 70%, 73%, 77%, 80%, 85%, etc., or a range consisting of any two of the above values, for example, it can be 70% to 73%, 77% to 85%, 80% to 85%, etc.
[0053] The proportion of the number of slender primary particles is within the above range, which can further improve the orderliness of the primary particle arrangement, reduce stress concentration between the primary particles, and make it easier to release stress.
[0054] In an embodiment of the present application, in a cross-sectional scanning electron microscope image of a secondary particle passing through the geometric center of the particle, the cross-section of a single secondary particle includes N1 primary particles; 250≤N1≤450.
[0055] When the size of the primary particles is within a suitable range, i.e., 0.1μm<P1≤3.5μm, 0.1μm≤P2≤0.6μm, the cross section of a single secondary particle includes the above number of primary particles. At this time, the number of primary particles contained in the secondary particles of the same size is more appropriate. During the battery cell cycle, the lithium ion deintercalation performance is better, stress release is easier, which is beneficial to reduce internal stress concentration and improve the battery's charge and discharge efficiency and cycle stability; at the same time, there are fewer crystal faces in contact with the electrolyte, fewer side reactions, and better electrochemical performance.
[0056] The number of primary particles is measured by the following method:
[0057] A scanning electron microscope (SEM) is used to take a cross-sectional electron microscope photograph of the secondary particle passing through the geometric center of the particle. A sector-shaped L1 region is selected on the cross-sectional surface of the secondary particle with the geometric center of the cross-sectional surface (e.g., the approximate center of a circle) as the endpoint. The area of the L1 region is one eighth of the total cross-sectional area. The number of primary particles in the L1 region is manually counted, and then 8 times the number is taken to obtain the number of primary particles included in each secondary particle.
[0058] Test method for the percentage of elongated primary particles based on the total number of primary particles in a single secondary particle:
[0059] Use a scanning electron microscope (SEM) to take a cross-sectional electron microscope photograph of the secondary particle passing through the geometric center of the particle, and select a sector L1 region on the cross section of the secondary particle with the geometric center of the cross section (for example, the approximate center of the circle) as the endpoint, and the area of the L1 region is one eighth of the total cross-sectional area. Manually count the number of primary particles in the L1 region and the number of slender primary particles in the L1 region; count the number of primary particles and the number of slender primary particles in the other seven regions in turn; add up the number of primary particles in the eight regions to obtain a first value, and add up the number of slender primary particles in the eight regions to obtain a second value, and the ratio of the second value to the first value is the proportion of the number of slender primary particles.
[0060] The longest diameter P1 and the shortest diameter P2 of the elongated primary particles are measured by observing the cross-section electron micrograph of the secondary particles passing through the geometric center of the particles.
[0061] For example, see Figure 1 , Figure 1 is a scanning electron microscope (SEM) photograph of positive electrode active material particles according to one embodiment of the present application. Figure 1 The particle size values of four elongated primary particles in the L1 region are given, and the L1 region also includes more elongated primary particles. Figure 1 As shown, in the L1 region, the longest diameter P1 of the elongated primary particles can be 1.31 μm, 1.50 μm, 1.90 μm, 2.64 μm, etc., the shortest diameter P2 can be 0.22 μm, 0.24 μm, 0.31 μm, 0.58 μm, etc., and P1 / P2 can be 4.57, 5.38, 6.05, 6.77, etc. The number of primary particles in the L1 region is 46, then Figure 1 The cross section of the secondary particles includes approximately 368 primary particles.
[0062] In the embodiment of the present application, the secondary particles are spherical in shape.
[0063] The morphology of secondary particles is spherical, which means that the morphology of secondary particles is close to a sphere, but there may be some irregularities. Figure 1 The cross section of the secondary particles of this embodiment is close to a circle, and the elongated primary particles in the secondary particles are arranged radially. The elongated primary particles are arranged radially so that the secondary particles are spherical in shape, and the secondary particles are less likely to crack.
[0064] In addition, if Figure 1 As shown, the positive electrode active material provided by the present application has primary particles arranged tightly inside the secondary particles without hollow structures or large pores. This arrangement is beneficial to improving the specific capacity of the positive electrode active material while reducing the risk of secondary particle breakage.
[0065] In the embodiment of the present application, the volume median particle size Dv50 of the secondary particles is 8.5 μm to 12 μm.
[0066] The volume median particle size Dv50 of the secondary particles can be 8.5 μm, 8.8 μm, 9 μm, 10 μm, 11 μm, 12 μm, etc., or a range consisting of any two of the above values, for example, 8.5 μm to 8.8 μm, 9 μm to 10 μm, 11 μm to 12 μm, etc. The volume median particle size Dv50 refers to the particle size value corresponding to the cumulative volume percentage reaching 50% in the volume distribution of the particles. The volume median particle size Dv50 is common knowledge in the art, has a meaning known in the art, and can be measured by methods and instruments in the art.
[0067] When the volume median particle size Dv50 of the secondary particles is within the above range, the contact area between the secondary particles and the electrolyte is small, which is beneficial to reduce the side reactions of the positive electrode active materials, thereby improving the cycle performance of the lithium-ion battery; at the same time, the diffusion of active lithium ions in the positive electrode active materials is also relatively easy, thereby taking into account the rate performance of the lithium-ion battery.
[0068] In the embodiment of the present application, the positive electrode active material includes a structural formula of Li a Ni b Co c Mn d M1 e O f material, wherein the M1 element includes one or more of Na, Mg, Zr, Al, Ca, W, Nb, Ta, Sr, K, Sb, Mo, W, 0.5≤a≤1.2, 0.85≤b≤0.99, 0<c≤0.1, 0<d≤0.05, 1.9≤f≤2.2, b+c+d+e=1.
[0069] Among them, lithium (Li) element provides lithium ions, which move between the positive and negative electrodes when the battery is charged and discharged, and are the key to battery energy storage and release. Nickel (Ni) element helps to improve the energy density of the positive electrode active material. In the above embodiment, nickel (Ni) element accounts for a high proportion of other metal elements except lithium element, so the positive electrode active material has a higher energy density. Cobalt (Co) element helps to stabilize the material structure, reduce impedance value, increase conductivity, and improve cycle and efficiency performance. Manganese (Mn) element can reduce material cost and improve the safety and stability of the material.
[0070] The doping element M1 helps to improve the bulk stability and electrical stability of the positive electrode active material, reduce the cation mixing problem caused by high nickel, and thus improve the electrochemical performance of the positive electrode active material.
[0071] In an embodiment of the present application, a first coating layer is formed on the surface of the positive electrode active material. The first coating layer includes a first element. The first element includes one or more of Co, Al, F, and Ti.
[0072] Among them, part of the first element is located on the surface of the positive electrode active material, and the other part penetrates into the interior of the positive electrode active material. The cobalt (Co) element can react with the residual alkali on the surface of the positive electrode active material and form a spinel-structured lithium cobalt oxide, which is beneficial to reduce the residual alkali and increase the three-dimensional lithium ion diffusion channel, thereby improving the lithium ion transport performance of the positive electrode active material. The aluminum (Al) element is beneficial to reduce the degree of cation mixing, improve the surface and interface stability of the positive electrode active material, and improve the thermal stability of the material. The fluorine (F) element is beneficial to alleviate the erosion of the surface electrolyte and improve the stability of the material. The titanium (Ti) element is beneficial to improve the strength of the material.
[0073] In summary, the first element is beneficial to improving the surface and interfacial stability of the positive electrode active material, thereby improving the electrochemical performance of the positive electrode active material.
[0074] In the embodiment of the present application, based on the molar amount of the positive electrode active material, the content of Co is 7000ppm to 15000ppm; and / or the content of Al is 300ppm to 1000ppm; and / or the content of F is 0 to 750ppm; and / or the content of Ti is 300ppm to 1000ppm. Within the above range, the first element can better improve the interface stability and electrochemical performance of the positive electrode active material. The content of the first element can be measured by inductively coupled plasma emission spectrometry (ICP).
[0075] In an embodiment of the present application, a second coating layer is formed on the surface of the positive electrode active material. The second coating layer includes a second element. The second element includes one or more of B, Al, and Y.
[0076] Among them, most of the second element is located on the surface of the positive electrode active material. Boron (B) element doping helps to form a stable oxygen octahedral structure, thereby improving the cycle stability and thermal stability of the material. Aluminum (Al) element is beneficial to reduce the degree of cation mixing, improve the surface stability of the positive electrode active material, and improve the thermal stability of the material. Yttrium (Y) element helps to enhance the corrosion resistance of the material and reduce the side reaction between the electrolyte and the material, thereby extending the service life of the battery.
[0077] In summary, the second element is beneficial to reducing the surface activity of the positive electrode active material, improving the surface stability of the positive electrode active material, and reducing the side reaction between the positive electrode active material and the electrolyte.
[0078] In the embodiment of the present application, based on the molar amount of the positive electrode active material, the content of the second element is 500ppm to 3000ppm. For example, it can be 500ppm, 1000ppm, 1200ppm, 1500ppm, 2400ppm, 2800ppm, 3000ppm, etc., or a range composed of any two of the above values, which can be 500ppm to 1000ppm, 1200ppm to 1500ppm, 2400ppm to 3000ppm, etc. Within the above range, the second element can better improve the surface stability and electrochemical properties of the positive electrode active material. The content of the second element can be measured by inductively coupled plasma emission spectrometer (ICP).
[0079] In one embodiment, the positive electrode active material may not include the first element and the second element. In another embodiment, the positive electrode active material may include only the first element. The first element may form a continuous first coating layer or a discontinuous first coating layer on the surface of the positive electrode active material. In another embodiment, the positive electrode active material may include the first element and the second element. The first element may form a continuous first coating layer or a discontinuous first coating layer on the surface of the positive electrode active material, and the second element may form a continuous second coating layer or a discontinuous second coating layer on the surface of the positive electrode active material. There is no obvious boundary between the first coating layer and the second coating layer.
[0080] In an embodiment of the present application, a positive electrode active material is also provided, the positive electrode active material includes lithium nickel cobalt manganese oxide, the molar proportion of nickel element in other metal elements except lithium element is greater than or equal to 85%; the positive electrode active material includes secondary particles, the secondary particles include primary particles, the primary particles include slender primary particles, the particle size of each slender primary particle includes a longest diameter P1 and a shortest diameter P2, 1.5≤P1 / P2≤10, 0.1μm<P1≤3.5μm, 0.1μm≤P2≤0.6μm; the slender primary particles are arranged radially.
[0081] By setting 1.5≤P1 / P2≤10, 0.1μm<P1≤3.5μm, 0.1μm≤P2≤0.6μm, the primary particles are slender primary particles, and the slender primary particles are arranged radially. When the volume of the primary particles changes during the charging and discharging process of the battery, the slender primary particles can be intertwined with each other, and the degree of mutual squeezing between the slender primary particles is relatively small, which is beneficial to alleviate the stress concentration caused by the volume change. At the same time, the radially arranged slender primary particles can expand and contract more evenly during the charging and discharging cycle, so that they have higher adaptability to deformation and can better transfer stress when deformation occurs; therefore, the stress concentration inside the secondary particles is low, and stress release is improved, thereby effectively alleviating the cracking inside the secondary particles, reducing the side reaction between the positive electrode particles and the electrolyte, and is beneficial to improving the cycle performance of the lithium-ion battery.
[0082] The molar proportion of nickel can be 85%, 88%, 90%, 95%, 99%, etc., or a range consisting of any two of the above values, for example, 85% to 88%, 85% to 90%, 90% to 95%, 95% to 99%, etc. The molar proportion of nickel in other metal elements except lithium is greater than or equal to 85%, which can effectively improve the specific capacity of the positive electrode active material, thereby helping to improve the energy density of lithium-ion batteries.
[0083] P1 / P1 can be 1.5, 1.6, 2, 3, 4.8, 5, 6, 7, 9, 10, etc., or a range consisting of any two of the above values, for example, it can be 1.5-1.6, 2-4.8, 1.5-6, 5-7, 9-10, etc. P1 / P2 is greater than or equal to 1.5, the longest diameter and the shortest diameter of the primary particles are quite different, and the shape is elongated. P1 can be 0.1μm, 0.15μm, 0.2μm, 0.35μm, 0.5μm, 1μm, 1.5μm, 2.2μm, 2.8μm, 3μm, 3.5μm, etc., or a range consisting of any two of the above values, for example, it can be 0.1μm-0.5μm, 0.15μm-0.35μm, 1μm-1.5μm, 2.2μm-2.8μm, 3μm-3.5μm, etc. P2 can be 0.1μm, 0.3μm, 0.4μm, 0.45μm, 0.5μm, 0.55μm, 0.6μm, etc., or a range consisting of any two of the above values, for example, it can be 0.3μm~0.4μm, 0.45μm~0.5μm, 0.55μm~0.6μm, etc.
[0084] In addition, when P1 and P2 of the elongated primary particles are within the above range, the elongated primary particles have a larger specific surface area than the spherical primary particles, and have more surfaces that can contact the electrolyte. The diffusion distance of lithium ions in the elongated primary particles is relatively short, which is beneficial to improving the transmission performance of lithium ions, so that lithium ions can be embedded and removed relatively quickly and evenly inside the positive electrode material, and the volume change of the positive electrode material during the charge and discharge process is relatively stable. When the longest diameter P1 of the elongated primary particles is less than 3.5μm, the diffusion path of lithium ions is shorter and the diffusion resistance is smaller, which is beneficial to improving the lithium ion transmission performance; when P1 is greater than 0.1μm, the preparation process of the positive electrode active material is less difficult and has fewer side reactions. The effect of the shortest diameter P2 of the elongated primary particles on the lithium ion diffusion performance is the same as above. At the same time, based on the value range of P1, the value range of P2 enables the value of P1 / P2 to meet the requirements of the elongated primary particles.
[0085] In one embodiment, 0.3 μm≤P1≤3.5 μm, and 0.1 μm≤P2≤0.6 μm. In this case, the difficulty of preparing the positive electrode active material can be further reduced, and side reactions can be reduced.
[0086] In the embodiment of the present application, based on the total number of primary particles in a single secondary particle, the number of elongated primary particles accounts for 60% to 85%. For example, it can be 60%, 62%, 65%, 73%, 77%, 85%, etc., or a range consisting of any two of the above values, for example, it can be 60% to 62%, 65% to 73%, 77% to 85%, etc.
[0087] At this time, most of the primary particles in the secondary particles are slender primary particles, which can improve the orderliness of the primary particle arrangement, further reduce the stress concentration between the primary particles, make it easier to release stress, effectively alleviate the cracking inside the secondary particles, reduce the occurrence of cracks in the positive electrode sheet, and improve the stability of the positive electrode sheet, which is beneficial to improving the cycle performance of lithium-ion batteries.
[0088] In the embodiments of the present application, a method for preparing a positive electrode active material is also provided. Figure 2 , Figure 2 It is a schematic flow chart of a method for preparing a positive electrode active material provided in the first embodiment of the present application.
[0089] The first embodiment provides a method for preparing a positive electrode active material, comprising:
[0090] S110: preparing a positive electrode active material precursor.
[0091] In the embodiment of the present application, the positive electrode active material precursor refers to nickel cobalt manganese hydroxide, and the positive electrode active material inherits the morphology and structure of the positive electrode active material precursor. Therefore, the structure design of the positive electrode active material can be achieved by designing the precursor.
[0092] The cathode active material precursor can be prepared by co-precipitation method, see Figure 3 , Figure 3 1 is a schematic flow chart of step S110 in the method for preparing the positive electrode active material provided in the first embodiment of the present application. S110 includes the following steps:
[0093] S111: preparing a mixed solution according to the molar ratio of Ni element, Co element and Mn element being b:c:d, 0.85≤b≤0.99, 0<c≤0.1, 0<d≤0.05.
[0094] In one embodiment, the source of the Ni element includes but is not limited to nickel carbonate, nickel hydroxide, nickel acetate, nickel sulfate, nickel chloride, nickel nitrate, nickel oxalate, etc.; the source of the Co element includes but is not limited to cobalt carbonate, cobalt hydroxide, cobalt acetate, cobalt sulfate, cobalt chloride, cobalt nitrate, cobalt oxalate, etc.; the source of the Mn element includes but is not limited to manganese dioxide, electrolytic manganese dioxide, manganese tetraoxide, etc.
[0095] In the embodiment of the present application, the Ni element accounts for more than 85% of the mixed solution, which helps to improve the energy density of the positive electrode active material. At the same time, the Co element helps to stabilize the material structure and improve the electrical conductivity. The Mn element can reduce the material cost and improve the safety and stability of the material.
[0096] S112: preparing a salt solution containing element U, wherein U includes one or more of B, F, Zr, W, and Al.
[0097] In one embodiment, the salt solution containing element U includes, but is not limited to, one or more of boric acid, ammonium fluoride, zirconium sulfate, ammonium metatungstate, sodium phosphotungstate, sodium tungstate, sodium metatungstate, potassium tungstate, and aluminum sulfate.
[0098] In one embodiment, the concentration of the salt solution containing element U is 0.01 mol / L to 1.5 mol / L.
[0099] In one embodiment, the mass proportion of the U element is 200 to 1000 ppm based on the total mass of the positive electrode active material.
[0100] The U element can induce the growth direction of the crystal during the growth of the positive electrode active material precursor, causing the primary particles to grow toward an elongated shape, thereby increasing the proportion of elongated primary particles in the positive electrode active material precursor.
[0101] S113: adding the mixed solution, the salt solution containing element U, the precipitant and the complexing agent into the reactor to carry out a coprecipitation reaction, wherein the volume median particle size Dv50 of the secondary particles of the positive electrode active material precursor is 8.5 μm to 12 μm.
[0102] In one embodiment, step S112 may be omitted, and the mixed solution, precipitant and complexing agent may be directly added to the reactor to perform a coprecipitation reaction, and the volume median particle size Dv50 of the secondary particles of the positive electrode active material precursor is 8.5 μm to 12 μm, thereby simplifying the preparation steps.
[0103] In one embodiment, the precipitant includes but is not limited to one or more of sodium carbonate, sodium hydroxide, potassium carbonate, and potassium hydroxide, and the precipitant helps separate the target component from the solution by forming a precipitate; the complexing agent includes but is not limited to one or more of ammonia water, ammonium chloride, ammonium sulfate, urea, citric acid, and ethylenediaminetetraacetic acid (EDTA), and the complexing agent can form a complex with the target substance to reduce its solubility in the solution. The precipitant and the complexing agent comprehensively regulate the pH of the coprecipitation reaction system.
[0104] By controlling the pH and temperature of the coprecipitation reaction system, it is beneficial to promote the growth of primary particles in the positive electrode active material precursor toward an elongated shape.
[0105] In one embodiment, the pH of the coprecipitation reaction system is 11 to 14. For example, it can be 11, 12, 12.5, 13, 14, etc., or a range consisting of any two of the above values, such as 11 to 12, 12 to 12.5, 13 to 14, etc. The pH of the coprecipitation reaction system within the above range is conducive to the refinement of primary particles.
[0106] In one embodiment, the pH of the coprecipitation reaction system is 11.2 to 12.5. For example, it can be 11.2, 11.5, 12, 12.2, 12.5, etc., or a range consisting of any two of the above values, such as 11.2 to 11.5, 12 to 12.2, 12.2 to 12.5, etc. The pH of the coprecipitation reaction system within the above range is conducive to further refinement of the primary particles.
[0107] In one embodiment, the temperature of the coprecipitation reaction system is 50° C. to 70° C. For example, it can be 50° C., 52° C., 55° C., 60° C., 65° C., 68° C., 70° C., etc., or a range consisting of any two of the above values, such as 50° C. to 52° C., 55° C. to 60° C., 65° C. to 70° C., etc. When the temperature of the coprecipitation reaction system is within the above range, the nucleation rate and growth rate of the primary particles can be adjusted, which is beneficial to the refinement of the primary particles.
[0108] In one embodiment, the temperature of the coprecipitation reaction system is 55° C. to 67° C. For example, it can be 55° C., 58° C., 60° C., 62° C., 65° C., 67° C., etc., or a range consisting of any two of the above values, such as 55° C. to 58° C., 60° C. to 62° C., 65° C. to 67° C., etc. The temperature of the coprecipitation reaction system within the above range is conducive to further refinement of the primary particles.
[0109] In one embodiment, the coprecipitation reaction ends when the secondary particles of the positive electrode active material precursor grow to a target particle size.
[0110] In one embodiment, the target particle size of the secondary particles of the positive electrode active material precursor is a volume median particle size Dv50, which has a value range of 8.5 μm to 12 μm. The volume median particle size Dv50 is common knowledge in the art, has a meaning known in the art, and can be measured by methods and instruments in the art.
[0111] The target particle size is within the above range, and the volume median particle size Dv50 of the secondary particles of the positive electrode active material can be controlled to be 8.5 μm to 12 μm, which is beneficial to reduce the side reactions of the positive electrode active material while taking into account the rate performance of the lithium ion battery.
[0112] After the coprecipitation reaction is completed, the product is washed and dried to obtain a positive electrode active material precursor.
[0113] S120: Mixing a positive electrode active material precursor, a lithium source and an M1 element source, and performing a first sintering to obtain a positive electrode active material; wherein the M1 element is one or more of Na, Mg, Zr, Al, Ca, W, Nb, Ta, Sr, K, Sb, Mo, and W.
[0114] In one embodiment, the lithium source includes but is not limited to one or more of LiOH·H2O, Li2CO3, Li2SO4, LiNO3, LiC2O4, and CH3COOLi, and any one of them can be used as a lithium source as long as it can provide lithium ions for the positive electrode active material in the first sintering.
[0115] In one embodiment, the ratio of the molar amount of the Li element to the sum of the molar amounts of the Ni element, the Co element, and the Mn element is 1.0 to 1.2.
[0116] In one embodiment, the M1 element source includes but is not limited to one or more of sodium carbonate, sodium hydroxide, zirconium hydroxide, zirconium oxide, zirconium carbonate, antimony sulfate, molybdenum sulfate, magnesium oxide, magnesium hydroxide, magnesium carbonate, titanium oxide, titanium hydroxide, titanium carbonate, tungsten oxide, tungsten hydroxide, potassium sulfate, tungsten carbonate, niobium oxide, niobium hydroxide, niobium carbonate, tantalum hydroxide, tantalum carbonate, strontium hydroxide, strontium oxide, strontium carbonate, strontium phosphate, calcium hydroxide, calcium oxide, calcium carbonate, calcium phosphate, aluminum oxide, and aluminum hydroxide.
[0117] In one embodiment, the temperature of the first sintering is 700°C to 800°C. For example, it can be 700°C, 720°C, 750°C, 760°C, 780°C, 800°C, etc., or a range consisting of any two of the above values, which can be 700°C to 720°C, 750°C to 760°C, 780°C to 800°C, etc. The higher temperature of the first sintering is conducive to the lithium element and the doping element to penetrate into the interior of the positive electrode active material precursor, react with the elements of the positive electrode active material precursor, and be uniformly distributed in the material body; it is conducive to the preparation and performance improvement of the positive electrode active material.
[0118] In one embodiment, the temperature of the first sintering is 720°C to 760°C. For example, it can be 720°C, 730°C, 750°C, 755°C, 760°C, etc., or a range consisting of any two of the above values, such as 720°C to 730°C, 750°C to 755°C, 750°C to 760°C, etc. By selecting the above first sintering temperature, it is beneficial to further uniformly distribute the lithium element and the doping element; it is further beneficial to the preparation and performance improvement of the positive electrode active material.
[0119] In one embodiment, the first sintering time is 7h to 14h. For example, it can be 7h, 8h, 10h, 12h, 14h, etc., or a range consisting of any two of the above values, which can be 7h to 8h, 10h to 12h, 12h to 14h, etc. By selecting the above first sintering time, it is beneficial to improve the doping effect of the M1 element.
[0120] The Li element provides lithium ions, which move between the positive and negative electrodes when the battery is charged and discharged, and are the key to battery energy storage and release; the doping element M1 helps to improve the bulk stability and electrical stability of the positive electrode active material, reduce the cation mixing problem caused by high nickel, and thus improve the electrochemical properties of the positive electrode active material; the first sintering temperature is relatively high, which is conducive to the uniform distribution of lithium and M1 elements in the bulk phase of the positive electrode active material, thereby improving the electrochemical properties and bulk stability of the positive electrode active material.
[0121] See also Figure 4 , Figure 4: is a schematic flow chart of a method for preparing a positive electrode active material provided in a second embodiment of the present application. The method for preparing a positive electrode active material provided in the second embodiment includes:
[0122] S210: preparing a positive electrode active material precursor.
[0123] The detailed steps of S210 may refer to S110 and will not be described in detail here.
[0124] S220: Mix a positive electrode active material precursor, a lithium source and an M1 element source, and perform a first sintering to obtain a positive electrode active material; wherein the M1 element is one or more of Na, Mg, Zr, Al, Ca, W, Nb, Ta, Sr, K, Sb, Mo, and W.
[0125] The detailed steps of S220 may refer to S120 and will not be described in detail here.
[0126] S230: Mixing the positive electrode active material with the first element source and performing a second sintering to form a first coating layer on the surface of the positive electrode active material, wherein the first coating layer includes a first element, and the first element includes one or more of Co, Al, F, and Ti.
[0127] In one embodiment, based on the molar amount of the positive electrode active material, the content of Co is 7000ppm to 15000ppm; and / or the content of Al is 300ppm to 1000ppm; and / or the content of F is 0 to 750ppm; and / or the content of Ti is 300ppm to 1000ppm.
[0128] Within the above range, the first element can better improve the interface stability and electrochemical performance of the positive electrode active material.
[0129] In one embodiment, the first element source includes but is not limited to one or more of cobalt oxyhydroxide, cobalt carbonate, cobalt hydroxide, cobalt acetate, cobalt sulfate, cobalt chloride, cobalt nitrate, cobalt oxalate, aluminum hydroxide, aluminum oxide, aluminum fluoride, titanium oxide, titanium hydroxide, and titanium carbonate.
[0130] In one embodiment, the temperature of the second sintering is 400°C to 650°C. For example, it can be 400°C, 450°C, 480°C, 500°C, 550°C, 600°C, 650°C, etc., or a range consisting of any two of the above values, such as 400°C to 480°C, 500°C to 550°C, 600°C to 650°C, etc. The temperature of the second sintering is lower than that of the first sintering, so a part of the first element is distributed on the surface of the positive electrode active material, and a part of it penetrates into the interior of the positive electrode active material.
[0131] In one embodiment, the second sintering time is 5h to 11h. For example, it can be 5h, 6h, 7.5h, 8.2h, 9h, 10h, 10.5h, 11h, etc., or a range consisting of any two of the above values, which can be 5h to 6h, 7.5h to 8.2h, 9h to 10h, 10.5h to 11h, etc. The second sintering time within the above range is conducive to improving the doping and coating effect of the first element.
[0132] The temperature and time of the second sintering are selected within the above range, so that part of the first element is distributed on the surface of the positive electrode active material, and part of it penetrates into the interior of the positive electrode active material, which is beneficial to improving the surface and interfacial stability of the positive electrode active material, thereby improving the electrochemical performance of the positive electrode active material.
[0133] S240: Wash and dry the product obtained in step S230.
[0134] In one embodiment, step S240 includes adding the product obtained in step S230 into water, stirring for 3 min to 5 min, and filtering and drying.
[0135] This embodiment is conducive to removing impurities on the surface of the positive electrode active material and improving product quality.
[0136] It should be noted that step S240 is an optional step, and whether to perform step S240 is determined according to needs.
[0137] See also Figure 5 , Figure 5 : is a schematic flow chart of a method for preparing a positive electrode active material provided in a third embodiment of the present application. The method for preparing a positive electrode active material provided in the third embodiment includes:
[0138] S310: preparing a positive electrode active material precursor.
[0139] The detailed steps of S310 may refer to S110 and will not be described in detail here.
[0140] S320: Mix a positive electrode active material precursor, a lithium source and an M1 element source, and perform a first sintering to obtain a positive electrode active material; wherein the M1 element is one or more of Na, Mg, Zr, Al, Ca, W, Nb, Ta, Sr, K, Sb, Mo, and W.
[0141] The detailed steps of S320 may refer to S120 and will not be described in detail here.
[0142] S330: Mixing the positive electrode active material with the first element source and performing a second sintering to form a first coating layer on the surface of the positive electrode active material, wherein the first coating layer includes a first element, and the first element includes one or more of Co, Al, F, and Ti.
[0143] The detailed steps of S330 may refer to S230 and will not be described again here.
[0144] S340: Wash and dry the product obtained in step S230.
[0145] The detailed steps of S330 may refer to S240 and will not be described in detail here.
[0146] S350: Mix the product obtained in step S340 with a second element source and perform a third sintering to form a second coating layer on the surface of the positive electrode active material, wherein the second coating layer includes a second element, and the second element includes one or more of B, Al, and Y.
[0147] In one embodiment, the content of the second element is less than or equal to 3000 ppm based on the molar amount of the positive electrode active material. Within the above range, the second element can better improve the surface stability and electrochemical performance of the positive electrode active material.
[0148] In one embodiment, the second element source includes, but is not limited to, one or more of boric acid, aluminum sulfate, yttrium oxide, and yttrium hydroxide.
[0149] In one embodiment, the temperature of the third sintering is 250°C to 400°C. For example, it can be 250°C, 280°C, 300°C, 320°C, 350°C, 360°C, 400°C, etc., or a range consisting of any two of the above values, such as 250°C to 280°C, 300°C to 350°C, 360°C to 400°C, etc. The temperature of the third sintering is lower than that of the second sintering, so most of the second element is coated on the surface of the positive electrode active material.
[0150] In one embodiment, the third sintering time is 5h to 12h. For example, it can be 5h, 6h, 7h, 8.5h, 10h, 11h, 12h, etc., or a range consisting of any two of the above values, such as 5h to 6h, 7h to 8.5h, 10h to 11h, etc. The third sintering time within the above range is conducive to improving the coating effect of the second element.
[0151] The temperature of the third sintering is lower than that of the second sintering, so most of the second element is coated on the surface of the positive electrode active material, which is beneficial to reduce the surface activity of the positive electrode active material, improve the surface stability of the positive electrode active material, and reduce the side reaction between it and the electrolyte.
[0152] In addition, the lithium-ion battery and electrical equipment of the present application will be described below with reference to the drawings as appropriate.
[0153] In the embodiment of the present application, in the lithium-ion battery, the isolation film is arranged between the positive electrode and the negative electrode, which mainly plays the role of preventing the positive and negative electrodes from short-circuiting, and at the same time allows ions to pass through. + The electrolyte is embedded and released back and forth between the positive electrode and the negative electrode, and plays the role of conducting ions between the positive electrode and the negative electrode.
[0154] The positive electrode sheet includes a positive electrode current collector and a positive electrode film layer arranged on at least one surface of the positive electrode current collector, and the positive electrode film layer includes the positive electrode active material of the above embodiment of the present application.
[0155] As an example, the positive electrode current collector has two surfaces opposite to each other in its thickness direction, and the positive electrode film layer is disposed on any one or both of the two opposite surfaces of the positive electrode current collector.
[0156] In some embodiments, the positive electrode current collector may be a metal foil or a composite current collector. For example, aluminum foil may be used as the metal foil. The composite current collector may include a polymer material base and a metal layer formed on at least one surface of the polymer material base. The composite current collector may be formed by forming a metal material (aluminum, aluminum alloy, nickel, nickel alloy, titanium, titanium alloy, silver and silver alloy, etc.) on a polymer material substrate (such as a substrate of polypropylene (PP), polyethylene terephthalate (PET), polybutylene terephthalate (PBT), polystyrene (PS), polyethylene (PE), etc.).
[0157] In some embodiments, the positive electrode film layer may also optionally include a binder. As an example, the binder may include at least one of polyvinylidene fluoride (PVDF), polytetrafluoroethylene (PTFE), vinylidene fluoride-tetrafluoroethylene-propylene terpolymer, vinylidene fluoride-hexafluoropropylene-tetrafluoroethylene terpolymer, tetrafluoroethylene-hexafluoropropylene copolymer, and fluorine-containing acrylate resin.
[0158] In some embodiments, the positive electrode film layer may further include a conductive agent, for example, the conductive agent may include at least one of superconducting carbon, acetylene black, carbon black, Ketjen black, carbon dots, carbon nanotubes, graphene and carbon nanofibers.
[0159] In some embodiments, the positive electrode sheet can be prepared in the following manner: the components for preparing the positive electrode sheet, such as the positive electrode active material, the conductive agent, the binder and any other components are dispersed in a solvent (such as N-methylpyrrolidone) to form a positive electrode slurry; the positive electrode slurry is coated on the positive electrode collector, and after drying, cold pressing and other processes, the positive electrode sheet can be obtained.
[0160] The negative electrode sheet includes a negative electrode current collector and a negative electrode film layer disposed on at least one surface of the negative electrode current collector, wherein the negative electrode film layer includes the negative electrode active material of the above embodiment.
[0161] As an example, the negative electrode current collector has two surfaces opposite to each other in its thickness direction, and the negative electrode film layer is disposed on any one or both of the two opposite surfaces of the negative electrode current collector.
[0162] In some embodiments, the negative electrode current collector may be a metal foil or a composite current collector. For example, as the metal foil, a copper foil may be used. The composite current collector may include a polymer material base layer and a metal layer formed on at least one surface of the polymer material substrate. The composite current collector may be formed by forming a metal material (copper, copper alloy, nickel, nickel alloy, titanium, titanium alloy, silver and silver alloy, etc.) on a polymer material substrate (such as a substrate of polypropylene (PP), polyethylene terephthalate (PET), polybutylene terephthalate (PBT), polystyrene (PS), polyethylene (PE), etc.).
[0163] In some embodiments, the negative electrode film layer may further include a binder. The binder may be selected from at least one of styrene-butadiene rubber (SBR), polyacrylic acid (PAA), sodium polyacrylate (PAAS), polyacrylamide (PAM), polyvinyl alcohol (PVA), sodium alginate (SA), polymethacrylic acid (PMAA) and carboxymethyl chitosan (CMCS).
[0164] In some embodiments, the negative electrode film layer may further include a conductive agent, which may be selected from at least one of superconducting carbon, acetylene black, carbon black, Ketjen black, carbon dots, carbon nanotubes, graphene and carbon nanofibers.
[0165] In some embodiments, the negative electrode film layer may optionally include other additives, such as a thickener (eg, sodium carboxymethyl cellulose (CMC-Na)).
[0166] In some embodiments, the negative electrode sheet can be prepared in the following manner: the components for preparing the negative electrode sheet, such as the negative electrode active material, the conductive agent, the binder and any other components are dispersed in a solvent (such as deionized water) to form a negative electrode slurry; the negative electrode slurry is coated on the negative electrode collector, and after drying, cold pressing and other processes, the negative electrode sheet can be obtained.
[0167] The electrolyte plays a role in conducting ions between the positive electrode and the negative electrode. The present application has no specific restrictions on the type of electrolyte, which can be selected according to needs.
[0168] In some embodiments, the electrolyte includes an electrolyte salt and a solvent.
[0169] In some embodiments, the electrolyte salt can be selected from at least one of lithium hexafluorophosphate, lithium tetrafluoroborate, lithium perchlorate, lithium hexafluoroarsenate, lithium bis(fluorosulfonyl)imide, lithium bis(trifluoromethanesulfonyl)imide, lithium trifluoromethanesulfonate, lithium difluorophosphate, lithium difluorooxalatoborate, lithium dioxalatoborate, lithium difluorodioxalatophosphate, and lithium tetrafluorooxalatophosphate.
[0170] In some embodiments, the solvent can be selected from at least one of ethylene carbonate, propylene carbonate, ethyl methyl carbonate, diethyl carbonate, dimethyl carbonate, dipropyl carbonate, methyl propyl carbonate, ethyl propyl carbonate, butylene carbonate, fluoroethylene carbonate, methyl formate, methyl acetate, ethyl acetate, propyl acetate, methyl propionate, ethyl propionate, propyl propionate, methyl butyrate, ethyl butyrate, 1,4-butyrolactone, cyclopentane sulfone, dimethyl sulfone, methyl ethyl sulfone and diethyl sulfone.
[0171] In some embodiments, the electrolyte may further include additives, such as negative electrode film-forming additives, positive electrode film-forming additives, and additives that can improve certain battery properties, such as additives that improve battery overcharge performance, additives that improve battery high or low temperature performance, etc.
[0172] In some embodiments, the material of the isolation membrane can be selected from at least one of glass fiber, non-woven fabric, polyethylene, polypropylene and polyvinylidene fluoride. The isolation membrane can be a single-layer film or a multi-layer composite film, without particular limitation. When the isolation membrane is a multi-layer composite film, the materials of each layer can be the same or different, without particular limitation.
[0173] In some embodiments, the positive electrode sheet, the negative electrode sheet, and the separator can be made into a battery cell assembly by a winding process or a lamination process.
[0174] In some embodiments, Figure 6 As shown, the lithium-ion battery 10 may include an outer package. The outer package can be used to encapsulate the battery cell assembly 11 and the electrolyte. The outer package includes an end cap 12, a shell 13 and other functional components.
[0175] The end cap 12 refers to a component that covers the opening of the shell 13 to isolate the internal environment of the lithium-ion battery 10 from the external environment. Without limitation, the shape of the end cap 12 can be adapted to the shape of the shell 13 to match the shell 13. Optionally, the end cap 12 can be made of a material with a certain hardness and strength (such as an aluminum alloy), so that the end cap 12 is not easily deformed when it is squeezed and collided, so that the lithium-ion battery 10 can have a higher structural strength and the safety performance can also be improved. Functional components such as electrode terminals 12a can be provided on the end cap 12. The electrode terminal 12a can be used to electrically connect to the battery cell assembly 11 for outputting or inputting electrical energy of the lithium-ion battery 10. In some embodiments, the end cap 12 can also be provided with a pressure relief mechanism for releasing the internal pressure when the internal pressure or temperature of the lithium-ion battery 10 reaches a threshold. The material of the end cap 12 can also be a variety of materials, including but not limited to copper, iron, aluminum, stainless steel, aluminum alloy, plastic, etc. In some embodiments, an insulating member (not shown) may be provided inside the end cap 12 to isolate the electrical connection components in the housing 13 from the end cap 12 to reduce the risk of short circuit. For example, the insulating member may be plastic, rubber, or the like.
[0176] The shell 13 is a component used to cooperate with the end cap 12 to form the internal environment of the lithium-ion battery 10, wherein the formed internal environment can be used to accommodate the battery cell assembly 11, the electrolyte and other components. The shell 13 and the end cap 12 can be independent components, and an opening can be set on the shell 13, and the internal environment of the lithium-ion battery 10 is formed by covering the opening with the end cap 12 at the opening. Without limitation, the end cap 12 and the shell 13 can also be integrated. Specifically, the end cap 12 and the shell 13 can form a common connection surface before other components enter the shell, and when the interior of the shell 13 needs to be encapsulated, the end cap 12 covers the shell 13. The shell 13 can be of various shapes and sizes, such as a rectangular parallelepiped, a cylindrical shape, a hexagonal prism, etc. Specifically, the shape of the shell 13 can be determined according to the specific shape and size of the battery cell assembly 11. The material of the shell 13 can be various, such as copper, iron, aluminum, stainless steel, aluminum alloy, plastic, etc., and the embodiment of the present application does not impose any special restrictions on this.
[0177] The housing 13 may contain one or more battery cell assemblies 11. The portions of the positive and negative electrodes that do not contain active materials each constitute a tab 11a. The positive tab and the negative tab may be located at one end of the main body or at both ends of the main body. During the charge and discharge process of the battery, the positive active material and the negative active material react with the electrolyte, and the tab 11a connects the electrode terminal to form a current loop.
[0178] Please refer to Figure 7 , Figure 7Schematic diagram of the exploded structure of the battery 100 provided in some embodiments of the present application. The battery 100 includes a box 20 and a lithium-ion battery 10, and the lithium-ion battery 10 is contained in the box 20. Among them, the box 20 is used to provide a storage space for the lithium-ion battery 10, and the box 20 can adopt a variety of structures. In some embodiments, the box 20 may include a first part 21 and a second part 22, the first part 21 and the second part 22 cover each other, and the first part 21 and the second part 22 jointly define a storage space for accommodating the lithium-ion battery 10. The second part 22 may be a hollow structure with one end open, the first part 21 may be a plate-like structure, and the first part 21 covers the open side of the second part 22, so that the first part 21 and the second part 22 jointly define a storage space; the first part 21 and the second part 22 may also be hollow structures with one side open, and the open side of the first part 21 covers the open side of the second part 22. Of course, the box 20 formed by the first part 21 and the second part 22 may be in a variety of shapes, such as a cylinder, a cuboid, etc.
[0179] In the battery 100, there may be multiple lithium-ion batteries 10, and the multiple lithium-ion batteries 10 may be connected in series, in parallel, or in a mixed connection. The mixed connection means that the multiple lithium-ion batteries 10 are both connected in series and in parallel. The multiple lithium-ion batteries 10 may be directly connected in series, in parallel, or in a mixed connection, and then the whole formed by the multiple lithium-ion batteries 10 is accommodated in the box 20; of course, the battery 100 may also be a battery module formed by connecting multiple lithium-ion batteries 10 in series, in parallel, or in a mixed connection, and then the multiple battery modules are connected in series, in parallel, or in a mixed connection to form a whole, and accommodated in the box 20. The battery 100 may also include other structures, for example, the battery 100 may also include a busbar component for realizing electrical connection between the multiple lithium-ion batteries 10.
[0180] The battery 100 in the embodiment of the present application includes a lithium-ion battery 10. In other embodiments, the battery 100 may further include any one or more of a lithium-sulfur battery, a sodium-ion battery, and a magnesium-ion battery, but is not limited thereto. The lithium-ion battery 10 may be cylindrical, flat, rectangular, or in other shapes.
[0181] In some embodiments, batteries may be assembled into a battery module. The number of batteries contained in the battery module may be one or more. The specific number may be selected by those skilled in the art according to the application and capacity of the battery module.
[0182] In addition, the present application also provides an electrical device, which includes at least one of the lithium-ion batteries and / or batteries provided in the present application. The lithium-ion battery or battery pack can be used as a power source for the electrical device, or as an energy storage unit for the electrical device. The electrical device may include mobile devices (such as mobile phones, laptops, etc.), electric vehicles (such as pure electric vehicles, hybrid electric vehicles, plug-in hybrid electric vehicles, electric bicycles, electric scooters, electric golf carts, electric trucks, etc.), electric trains, ships and satellites, energy storage systems, etc., but are not limited thereto.
[0183] As an electrical device, a lithium-ion battery and / or a battery can be selected according to its usage requirements.
[0184] Figure 8a and Figure 8b As shown, it is an electric device as an example. The electric device is a vehicle such as a pure electric vehicle, a hybrid electric vehicle or a plug-in hybrid electric vehicle. A structural schematic diagram of a vehicle 1000 is specifically provided. A battery 100 is arranged inside the vehicle 1000, and the battery 100 can be arranged at the bottom, head or tail of the vehicle 1000. The battery 100 can be used to power the vehicle 1000. For example, the battery 100 can be used as an operating power source for the vehicle 1000. The vehicle 1000 may also include a controller 200 and a motor 300. The controller 200 is used to control the battery 100 to power the motor 300, for example, for the working power demand of the vehicle 1000 during starting, navigation and driving.
[0185] In some embodiments of the present application, the battery 100 can not only serve as an operating power source for the vehicle 1000, but also serve as a driving power source for the vehicle 1000, replacing or partially replacing fuel or natural gas to provide driving power for the vehicle 1000.
[0186] Hereinafter, the embodiments of the present application will be described. The embodiments described below are exemplary and are only used to explain the present application, and should not be construed as limiting the present application. If no specific techniques or conditions are indicated in the embodiments, the techniques or conditions described in the literature in this area or the product specifications are used. If the manufacturer is not indicated in the reagents or instruments used, they are all conventional products that can be obtained commercially.
[0187] Example 1
[0188] Preparation method of positive electrode active material:
[0189] 1. A mixed solution containing Ni, Co and Mn elements was prepared by mixing them in a molar ratio of 0.93:0.06:0.01 among Ni, Co and Mn; the mixed solution, sodium carbonate and ammonia water were added into a reactor at a certain pump speed, the pH in the reactor was controlled to be 11.5 and the temperature was controlled to be 57°C, and a coprecipitation reaction was performed to make the particles of the precursor grow to the target Dv50=8.8μm. After the reaction was completed, the precursor was washed and dried to obtain an ultra-high nickel ternary material precursor.
[0190] 2. The lithium source and the ultra-high nickel ternary material precursor synthesized in step 1 are mixed in a molar ratio of 1:0.9996, and yttrium hydroxide, a doping element source, is added to make the molar ratio of Li and Y be 1:0.0004, and the mixture is fully mixed to obtain a mixture, and the mixture is sintered once at a high temperature of 725°C and a sintering time of 13h to obtain an ultra-high nickel ternary positive electrode material Li (Ni 0.93 Co 0.06 Mn 0.01 ) 0.9996 Y 0.0004 O2.
[0191] Preparation method of positive electrode sheet:
[0192] The positive electrode active material Li(Ni 0.93 Co 0.06 Mn 0.01 ) 0.9996 Y 0.0004 O2, conductive carbon black (Super-P) and polyvinylidene fluoride (PVDF) are mixed with N, N-dimethylpyrrolidone (NMP) in a weight ratio of 98:0.5:1.5, and stirred evenly to obtain the slurry of the positive electrode sheet, and the slurry of the positive electrode sheet is evenly coated on both sides of the aluminum foil, and the thickness of the aluminum foil is 60μm. The electrode sheet is cold pressed and sliced to obtain the positive electrode sheet, and the thickness of the positive electrode sheet is 0.120mm.
[0193] Among them, Li(Ni 0.93 Co 0.06 Mn 0.01 ) 0.9996 Y 0.0004 O2 is used as the positive electrode active material, conductive carbon black (Super-P) is used as the conductive agent, polyvinylidene fluoride (PVDF) is used as the binder, and N,N-dimethylpyrrolidone (NMP) is used as the slurry solvent.
[0194] Preparation method of negative electrode sheet:
[0195] In the embodiment of the present application, the negative electrode active material, the conductive agent, the thickener and the binder are mixed with deionized water to form a slurry of the negative electrode sheet. Specifically, in the embodiment of the present application, the negative electrode active material is artificial graphite and hard carbon, the conductive agent is acetylene black, the thickener is sodium carboxymethyl cellulose (CMC-Na), and the binder is styrene-butadiene rubber (SBR).
[0196] Artificial graphite, hard carbon, conductive agent acetylene black, binder styrene butadiene rubber (SBR) and thickener sodium carbon methyl cellulose (CMC-Na) are added to the deionized water solvent in a mass ratio of 90:5:2:2:1 and stirred and mixed evenly. The slurry for coating the negative electrode sheet is obtained by stirring evenly. The viscosity can be adjusted by deionized water during the stirring process. Then, the slurry is coated on both sides of the negative electrode collector with a certain width, and the negative electrode sheet is obtained by cold pressing and slicing. In the embodiment of the present application, the negative electrode collector is a 6μm thick copper foil.
[0197] Preparation method of lithium ion secondary battery:
[0198] The positive electrode sheet, the separator and the negative electrode sheet are wound into a battery cell assembly, and a lithium-ion secondary battery is obtained through the welding of the pole ears, packaging with an aluminum shell, liquid injection, packaging formation and vacuum molding. The injected electrolyte is a mixture of ethylene carbonate (EC), diethyl carbonate (DEC) and dimethyl carbonate (DMC), wherein the volume ratio of EC, DEC and DMC is 1:1:1. Then LiPF6 is dissolved in the above organic solvent, wherein the concentration of LiPF6 is 1 mol / L, and the separator adopts a polyethylene film with a thickness of 13 μm.
[0199] Example 2
[0200] The lithium ion battery and the method for preparing the lithium ion battery in the embodiment of the present application are different from those in Example 1 in the method for preparing the positive electrode active material, which is specifically as follows:
[0201] 1. A mixed solution containing Ni, Co and Mn elements was prepared by mixing them in a molar ratio of 0.93:0.06:0.01 among Ni, Co and Mn; the mixed solution, sodium carbonate and ammonia water were added into a reactor at a certain pump speed, the pH in the reactor was controlled to be 11.5 and the temperature was controlled to be 57°C, and a coprecipitation reaction was performed to make the particles of the precursor grow to the target Dv50=8.8μm. After the reaction was completed, the precursor was washed and dried to obtain an ultra-high nickel ternary material precursor.
[0202] 2. Mix the lithium source with the ultra-high nickel ternary material precursor synthesized in step 1 in a molar ratio of 1:0.9991, add doping element sources zirconium sulfate and yttrium hydroxide to make the molar ratio of Li, Y, and Zr be 1:0.0004:0.0005, mix well to obtain a mixture, and sinter once at a high temperature of 725°C and a sintering time of 13 hours to obtain an ultra-high nickel ternary positive electrode material.
[0203] 3. Mix the ultra-high nickel ternary positive electrode material obtained in step 2 with the first element source CoOOH and TiO2 so that the molar ratio of Li, Co, and Ti is 1:0.01:0.001, and sinter at high temperature. The sintering temperature is 620°C and the sintering time is 7.5h to obtain an ultra-high nickel ternary positive electrode material with Co and Ti coated on the surface.
[0204] 4. Add the high-nickel ternary positive electrode material obtained in step 3 to the aqueous solution and stir for 4 minutes, and filter and dry to obtain the product.
[0205] The rest is the same as that of Example 1 and will not be described again.
[0206] Example 3
[0207] The lithium ion battery and the method for preparing the lithium ion battery in the embodiment of the present application are different from those in Example 1 in the method for preparing the positive electrode active material, which is specifically as follows:
[0208] 1. A mixed solution containing Ni, Co and Mn elements was prepared according to a molar ratio of Ni, Co and Mn of 0.93:0.06:0.01; the mixed solution, sodium carbonate and ammonia water were added to a reactor at a certain pump speed, the pH in the reactor was controlled to be 11.3, the temperature was controlled to be 57°C, and a coprecipitation reaction was performed to make the precursor particles grow to the target Dv50=11.6μm. After the reaction was completed, the precursor was washed and dried to obtain an ultra-high nickel ternary material precursor.
[0209] 2. The lithium source and the ultra-high nickel ternary material precursor synthesized in step 1 are mixed in a molar ratio of 1:0.9991, and zirconium sulfate and yttrium hydroxide, the doping element sources, are added to make the molar ratio of Li, Y, and Zr be 1:0.0004:0.0005, and the mixture is fully mixed, and the mixture is sintered at a high temperature of 725°C and a sintering time of 13h to obtain the ultra-high nickel ternary positive electrode material Li (Ni 0.93 Co 0.06 Mn 0.01 ) 0.9991 Y 0.0004 Zr 0.0005 O2.
[0210] 3. The ultra-high nickel ternary positive electrode material obtained in step 2 is mixed with CoOOH and TiO2 so that the molar ratio of Li, Co and Ti is 1:0.01:0.001, and sintered at high temperature. The sintering temperature is 620°C and the sintering time is 7.5h to obtain an ultra-high nickel ternary positive electrode material with Co and Ti coated on the surface.
[0211] 4. Add the high-nickel ternary positive electrode material obtained in step 3 to the aqueous solution and stir for 4 minutes, and filter and dry to obtain the product.
[0212] 5. The ultra-high nickel ternary positive electrode material obtained in step 4 is mixed with the second element source H2BO3 so that the molar ratio of Li and B is 1:0.001, and sintered at high temperature. The sintering temperature is 350°C and the sintering time is 6 hours to obtain an ultra-high nickel ternary positive electrode material with B coated on the surface.
[0213] The rest is the same as that of Example 1 and will not be described again.
[0214] Example 4
[0215] The lithium ion battery and the method for preparing the lithium ion battery in the embodiment of the present application are different from those in Example 1 in the method for preparing the positive electrode active material, which is specifically as follows:
[0216] 1. A mixed solution containing Ni, Co and Mn elements was prepared according to a molar ratio of Ni, Co and Mn of 0.93:0.06:0.01, and an ammonium metatungstate solution was prepared with a concentration of 0.6 mol / L, and a molar ratio of U element to Ni element of 0.0006:1; under a certain pump speed, the mixed solution, salt solution, sodium carbonate and ammonia water were added to the reactor, and the pH in the reactor was controlled to be 11.6 and the temperature was 59°C to carry out a coprecipitation reaction so that the particles of the precursor grew to the target Dv50=8.9 μm. After the reaction was completed, the precursor was washed and dried to obtain an ultra-high nickel ternary material precursor.
[0217] 2. The lithium source and the ultra-high nickel ternary material precursor synthesized in step 1 are mixed in a molar ratio of 1:0.9991, and zirconium sulfate and yttrium hydroxide, the doping element sources, are added to make the molar ratio of Li, Y, and Zr be 1:0.0004:0.0005, and the mixture is fully mixed, and the mixture is sintered at a high temperature of 725°C and a sintering time of 13h to obtain the ultra-high nickel ternary positive electrode material Li (Ni 0.93 Co 0.06 Mn 0.01 ) 0.9991 Y 0.0004 Zr 0.0005 O2.
[0218] 3. The ultra-high nickel ternary positive electrode material obtained in step 2 is mixed with CoOOH and TiO2 so that the molar ratio of Li, Co and Ti is 1:0.011:0.001, and sintered at high temperature. The sintering temperature is 620°C and the sintering time is 7.5h to obtain an ultra-high nickel ternary positive electrode material with Co and Ti coated on the surface.
[0219] 4. Add the high-nickel ternary positive electrode material obtained in step 3 to the aqueous solution and stir for 4 minutes, and filter and dry to obtain the product.
[0220] 5. The ultra-high nickel ternary positive electrode material obtained in step 4 is mixed with the second element source H2BO3 and Al2O3 so that the molar ratio of Li, B and Al is 1:0.001:0.0004, and sintered at high temperature. The sintering temperature is 350°C and the sintering time is 6 hours to obtain an ultra-high nickel ternary positive electrode material with B and Al coated on the surface.
[0221] The rest is the same as that of Example 1 and will not be described again.
[0222] Example 5
[0223] The lithium ion battery and the method for preparing the lithium ion battery in the embodiment of the present application are different from those in Example 1 in the method for preparing the positive electrode active material, which is specifically as follows:
[0224] 1. A mixed solution containing Ni, Co and Mn elements is prepared according to a molar ratio of Ni, Co and Mn of 0.93:0.06:0.01, and a salt solution of ammonium metatungstate and boric acid is prepared. The concentration of the ammonium metatungstate solution is 0.6 mol / L, the concentration of the boric acid solution is 0.5 mol / L, the concentration is 0.01 mol / L-1.5 mol / L, and the molar ratio of the U element (the sum of the W element and the B element) to the Ni element is 0.001:1; at a certain pump speed, the mixed solution, the salt solution, sodium carbonate and ammonia water are added to the reactor, the pH in the reactor is controlled to be 11.8, the temperature is 61°C, and a coprecipitation reaction is carried out to make the particles of the precursor grow to the target Dv50=8.8 μm. After the reaction is completed, washing and drying are carried out to obtain an ultra-high nickel ternary material precursor.
[0225] 2. The lithium source and the ultra-high nickel ternary material precursor synthesized in step 1 are mixed in a molar ratio of 1:0.9972, and doping element sources zirconium sulfate, antimony sulfate, and tantalum carbonate are added to make the molar ratio of Li, Sb, Zr, and Ta be 1:0.0008:0.001:0.001. The mixture is fully mixed and sintered at a high temperature of 735°C for 13 hours to obtain an ultra-high nickel ternary positive electrode material Li (Ni 0.93 Co 0.06 Mn 0.01 )0.9972 Sb 0.0008 Zr 0.001 Ta 0.001 O2.
[0226] 3. The ultra-high nickel ternary positive electrode material obtained in step 2 is mixed with CoOOH and Al2O3 so that the molar ratio of Li, Co and Al is 1:0.011:0.001, and sintered at high temperature. The sintering temperature is 620°C and the sintering time is 7.5h to obtain an ultra-high nickel ternary positive electrode material with Co and Al coated on the surface.
[0227] 4. Add the high-nickel ternary positive electrode material obtained in step 3 to the aqueous solution and stir for 4 minutes, and filter and dry to obtain the product.
[0228] 5. The ultra-high nickel ternary positive electrode material obtained in step 4 is mixed with the second element source H2BO3 so that the molar ratio of Li and B is 1:0.0015, and sintered at high temperature. The sintering temperature is 350°C and the sintering time is 6 hours to obtain an ultra-high nickel ternary positive electrode material with B coated on the surface.
[0229] The rest is the same as that of Example 1 and will not be described again.
[0230] Example 6
[0231] The lithium ion battery and the method for preparing the lithium ion battery in the embodiment of the present application are different from those in Example 1 in the method for preparing the positive electrode active material, which is as follows:
[0232] 1. A mixed solution containing Ni, Co and Mn elements was prepared according to a molar ratio of Ni, Co and Mn of 0.93:0.06:0.01, and an ammonium metatungstate solution was prepared with a concentration of 0.6 mol / L, and a molar ratio of U element (W element) to Ni element of 0.0006:1; at a certain pump speed, the mixed solution, salt solution, sodium carbonate and ammonia water were added to the reactor, and the pH in the reactor was controlled to be 11.6 and the temperature was 59°C to carry out a coprecipitation reaction so that the particles of the precursor grew to the target Dv50=8.8 μm. After the reaction was completed, the precursor was washed and dried to obtain an ultra-high nickel ternary material precursor.
[0233] 2. The lithium source and the ultra-high nickel ternary material precursor synthesized in step 1 are mixed in a molar ratio of 1:0.9981, and doping element sources zirconium sulfate, yttrium hydroxide, and tantalum carbonate are added to make the molar ratio of Li, Y, Zr, and Ta be 1:0.0004:0.0005:0.001. The mixture is fully mixed and sintered at a high temperature of 725°C for 13.5 hours to obtain an ultra-high nickel ternary positive electrode material Li (Ni 0.93 Co 0.06 Mn0.01 ) 0.9981 Y 0.0004 Zr 0.0005 Ta 0.001 O2.
[0234] 3. The ultra-high nickel ternary positive electrode material obtained in step 2 is mixed with CoOOH and TiO2 so that the molar ratio of Li, Co and Ti is 1:0.01:0.001, and sintered at high temperature. The sintering temperature is 620°C and the sintering time is 7.5h to obtain an ultra-high nickel ternary positive electrode material with Co and Ti coated on the surface.
[0235] 4. Add the high-nickel ternary positive electrode material obtained in step 3 to the aqueous solution and stir for 4 minutes, and filter and dry to obtain the product.
[0236] 5. The ultra-high nickel ternary positive electrode material obtained in step 4 is mixed with the second element source H2BO3 and Y2O3 so that the molar ratio of Li, B, and Y is 1:0.001:0.0006, and sintered at a high temperature of 350°C for 6 hours to obtain an ultra-high nickel ternary positive electrode material with B and Y coated on the surface.
[0237] The rest is the same as that of Example 1 and will not be described again.
[0238] Example 7
[0239] The lithium ion battery and the method for preparing the lithium ion battery in the embodiment of the present application are different from those in Example 1 in the method for preparing the positive electrode active material, which is as follows:
[0240] 1. A mixed solution containing Ni, Co and Mn elements was prepared according to a molar ratio of Ni, Co and Mn of 0.93:0.06:0.01; the mixed solution, sodium carbonate and ammonia water were added to a reactor at a certain pump speed, the pH in the reactor was controlled to be 11.6, the temperature was controlled to be 59°C, and a coprecipitation reaction was carried out to make the particles of the precursor grow to the target Dv50=8.8μm. After the reaction was completed, the precursor was washed and dried to obtain an ultra-high nickel ternary material precursor.
[0241] 2. The lithium source and the ultra-high nickel ternary material precursor synthesized in step 1 are mixed in a molar ratio of 1:0.9983, and doping element sources zirconium sulfate, yttrium hydroxide, and tantalum carbonate are added to make the molar ratio of Li, Y, Zr, and Ta be 1:0.0004:0.0008:0.0005. The mixture is fully mixed and sintered at a high temperature of 725°C for 13.5 hours to obtain an ultra-high nickel ternary positive electrode material Li (Ni 0.93 Co 0.06 Mn 0.01 ) 0.9983Y 0.0004 Zr 0.0008 Ta 0.0005 O2.
[0242] 3. The ultra-high nickel ternary positive electrode material obtained in step 2 is mixed with CoOOH and TiO2 so that the molar ratio of Li, Co and Ti is 1:0.01:0.001, and sintered at high temperature. The sintering temperature is 620°C and the sintering time is 7.5h to obtain an ultra-high nickel ternary positive electrode material with Co and Ti coated on the surface.
[0243] 4. Add the high-nickel ternary positive electrode material obtained in step 3 to the aqueous solution and stir for 4 minutes, and filter and dry to obtain the product.
[0244] 5. The ultra-high nickel ternary positive electrode material obtained in step 4 is mixed with the second element source H2BO3 so that the molar ratio of Li and B is 1:0.001, and sintered at high temperature. The sintering temperature is 350°C and the sintering time is 6 hours to obtain an ultra-high nickel ternary positive electrode material with B coated on the surface.
[0245] The rest is the same as that of Example 1 and will not be described again.
[0246] Example 8
[0247] The lithium ion battery and the method for preparing the lithium ion battery in the embodiment of the present application are different from those in Example 1 in the method for preparing the positive electrode active material, which is as follows:
[0248] 1. A mixed solution containing Ni, Co and Mn elements was prepared according to a molar ratio of Ni, Co and Mn of 0.93:0.06:0.01, and an ammonium metatungstate solution was prepared with a concentration of 0.6 mol / L, and a molar ratio of U element (W element) to Ni element of 0.0006:1; at a certain pump speed, the mixed solution, salt solution, sodium carbonate and ammonia water were added to the reactor, and the pH in the reactor was controlled to be 11.6 and the temperature was 59°C to carry out a coprecipitation reaction so that the particles of the precursor grew to the target Dv50=8.8 μm. After the reaction was completed, the precursor was washed and dried to obtain an ultra-high nickel ternary material precursor.
[0249] 2. The lithium source and the ultra-high nickel ternary material precursor synthesized in step 1 are mixed in a molar ratio of 1:0.9981, and doping element sources zirconium sulfate, yttrium hydroxide, and tantalum carbonate are added to make the molar ratio of Li, Y, Zr, and Ta be 1:0.0004:0.0005:0.001. The mixture is fully mixed and sintered at a high temperature of 725°C for 13.5 hours to obtain an ultra-high nickel ternary positive electrode material Li (Ni 0.93 Co 0.06 Mn 0.01 )0.9981 Y 0.0004 Zr 0.0005 Ta 0.001 O2.
[0250] 3. Mix the ultra-high nickel ternary positive electrode material obtained in step 2 with CoOOH, Al2O3 and TiO2 so that the molar ratio of Li, Co, Ti and Al is 1:0.01:0.0006:0.0004, and sinter them at high temperature. The sintering temperature is 630°C and the sintering time is 7h to obtain an ultra-high nickel ternary positive electrode material coated with Co, Al and Ti on the surface.
[0251] 4. Add the high-nickel ternary positive electrode material obtained in step 3 to the aqueous solution and stir for 4 minutes, and filter and dry to obtain the product.
[0252] 5. The ultra-high nickel ternary positive electrode material obtained in step 4 is mixed with the second element source H2BO3 so that the molar ratio of Li and B is 1:0.001, and sintered at high temperature. The sintering temperature is 350°C and the sintering time is 6 hours to obtain an ultra-high nickel ternary positive electrode material with B coated on the surface.
[0253] The rest is the same as that of Example 1 and will not be described again.
[0254] Example 9
[0255] The lithium ion battery and the method for preparing the lithium ion battery in the embodiment of the present application are different from those in Example 1 in the method for preparing the positive electrode active material, which is as follows:
[0256] 1. A mixed solution containing Ni, Co and Mn elements was prepared according to a molar ratio of Ni, Co and Mn of 0.93:0.06:0.01, and an ammonium metatungstate solution was prepared with a concentration of 0.6 mol / L, and a molar ratio of U element (W element) to Ni element of 0.0006:1; at a certain pump speed, the mixed solution, salt solution, sodium carbonate and ammonia water were added to the reactor, and the pH in the reactor was controlled to be 11.6 and the temperature was 59°C to carry out a coprecipitation reaction so that the particles of the precursor grew to the target Dv50=8.8 μm. After the reaction was completed, the precursor was washed and dried to obtain an ultra-high nickel ternary material precursor.
[0257] 2. The lithium source and the ultra-high nickel ternary material precursor synthesized in step 1 are mixed in a molar ratio of 1:0.9981, and doping element sources zirconium sulfate, yttrium hydroxide, and tantalum carbonate are added to make the molar ratio of Li, Y, Zr, and Ta be 1:0.0004:0.0005:0.001. The mixture is fully mixed and sintered at a high temperature of 725°C for 13.5 hours to obtain an ultra-high nickel ternary positive electrode material Li (Ni 0.93 Co0.06 Mn 0.01 ) 0.9981 Y0 .0004 Zr 0.0005 Ta 0.001 O2.
[0258] 3. The ultra-high nickel ternary positive electrode material obtained in step 2 is mixed with CoOOH, Al2O3 and TiO2 so that the molar ratio of Li, Co, Ti and Al is 1:0.01:0.0001:0.0008, and sintered at high temperature, the sintering temperature is 620°C, and the sintering time is 7.5h to obtain an ultra-high nickel ternary positive electrode material coated with Co, Al and Ti on the surface.
[0259] 4. Add the high-nickel ternary positive electrode material obtained in step 3 to the aqueous solution and stir for 4 minutes, and filter and dry to obtain the product.
[0260] 5. The ultra-high nickel ternary positive electrode material obtained in step 4 is mixed with the second element source H2BO3 so that the molar ratio of Li and B is 1:0.0015, and sintered at high temperature. The sintering temperature is 365°C and the sintering time is 5 hours to obtain an ultra-high nickel ternary positive electrode material with B coated on the surface.
[0261] The rest is the same as that of Example 1 and will not be described again.
[0262] Comparative Example
[0263] The lithium ion battery and the preparation method of the lithium ion battery of the comparative example of the present application are different from those of Example 1 in the preparation method of the positive electrode active material, which is as follows:
[0264] 1. A mixed solution containing Ni, Co and Mn elements was prepared according to a molar ratio of Ni, Co and Mn of 0.93:0.06:0.01; the mixed solution, sodium carbonate and ammonia water were added to a reactor at a certain pump speed, the pH in the reactor was controlled to be 10.5, the temperature was controlled to be 50°C, and a coprecipitation reaction was carried out to make the particles of the precursor grow to the target Dv50=8.8μm. After the reaction was completed, the precursor was washed and dried to obtain an ultra-high nickel ternary material precursor.
[0265] 2. The lithium source and the ultra-high nickel ternary material precursor synthesized in step 1 are mixed in a molar ratio of 1:0.9996, and yttrium hydroxide, a doping element source, is added to make the molar ratio of Li and Y be 1:0.0004, and the mixture is fully mixed to obtain a mixture, and the mixture is sintered once at a high temperature of 725°C and a sintering time of 13h to obtain an ultra-high nickel ternary positive electrode material Li (Ni 0.93 Co 0.06 Mn 0.01 ) 0.9996 Y0.0004 O2.
[0266] 3. The ultra-high nickel ternary positive electrode material obtained in step 2 is mixed with CoOOH so that the molar ratio of Li to Co is 1:0.007, and sintered at high temperature. The sintering temperature is 620°C and the sintering time is 7.5h to obtain an ultra-high nickel ternary positive electrode material with Co coated on the surface.
[0267] 4. Add the high-nickel ternary positive electrode material obtained in step 3 to the aqueous solution and stir for 4 minutes, and filter and dry to obtain the product.
[0268] 5. The ultra-high nickel ternary positive electrode material obtained in step 4 is mixed with the second element source H2BO3 so that the molar ratio of Li and B is 1:0.0007, and sintered at high temperature. The sintering temperature is 350°C and the sintering time is 6 hours to obtain an ultra-high nickel ternary positive electrode material with B coated on the surface.
[0269] The rest is the same as that of Example 1 and will not be described again.
[0270] Test Method
[0271] 1. Number of primary particles (N1), longest diameter (P1) and shortest diameter (P2)
[0272] Use a scanning electron microscope (SEM) to take a cross-sectional electron microscope photograph of the secondary particle passing through the geometric center of the particle, and select a sector L1 region on the cross section of the secondary particle with the geometric center of the cross section (for example, the approximate center of the circle) as the endpoint. The area of the L1 region is one eighth of the total cross-sectional area. Manually count the number of primary particles in the L1 region, and then take 8 times the number to obtain the number of primary particles included in each secondary particle, and measure the longest diameter (P1) and shortest diameter (P2) of the primary particles in turn.
[0273] 2. Volume median particle size Dv50
[0274] The particle size is determined by laser diffraction analysis, and can be determined by using a laser particle size analyzer (such as Malvern Master Size 3000) in accordance with the standard GB / T 19077-2016.
[0275] 3. Lithium-ion battery cycle performance
[0276] The lithium-ion battery was allowed to stand at 25°C for 5 minutes; charged at 0.5C constant current to 4.25V; charged at 0.05C constant voltage to 4.25V, and discharged at 0.5C constant current to 2.8V, and the initial capacity was obtained by testing, which was recorded as C0; the battery was allowed to stand at 25°C for 10 minutes; the above charge and discharge steps were repeated to cycle the battery for 100 times, and the capacity after 100 cycles was tested, which was recorded as C100, and the capacity retention rate = C100 / C0*100%.
[0277]
[0278] According to the test results in Table 1, compared with the comparative example in which the shape of the primary particles is close to spherical, the positive electrode active material provided in this case includes slender primary particles, and the proportion of slender primary particles in the secondary particles is 60% to 85%, which improves the stress release process of the positive electrode active material during the battery cell cycle and reduces stress accumulation. Therefore, the stability of the positive electrode active material is better, and the lithium-ion battery using the positive electrode active material shows better cycle performance.
[0279] In addition, compared with Example 1 and Example 2, the cycle retention rates of Examples 3 to 9 are better, indicating that the first element and the second element further improve the stability of the positive electrode active material, thereby further improving the cycle performance of the lithium ion battery.
[0280] It should be noted that the present application is not limited to the above-mentioned embodiments. The above-mentioned embodiments are only examples, and the embodiments having the same structure as the technical idea and exerting the same effect within the scope of the technical solution of the present application are all included in the technical scope of the present application. In addition, without departing from the scope of the main purpose of the present application, various modifications that can be thought of by those skilled in the art to the embodiments and other methods of combining some of the constituent elements in the embodiments are also included in the scope of the present application.
Claims
1. A lithium ion battery, characterized in that: The invention comprises a shell, a battery cell assembly and an electrolyte disposed in the shell, wherein the battery cell assembly is located in the electrolyte, the battery cell assembly comprises a positive electrode sheet, a negative electrode sheet and a separator, wherein the separator is located between the positive electrode sheet and the negative electrode sheet, the positive electrode sheet comprises a positive electrode current collector and a positive electrode film layer disposed on at least one side of the positive electrode current collector, the positive electrode film layer comprises a positive electrode active material, the positive electrode active material comprises lithium nickel cobalt manganese oxide, and the molar proportion of nickel in other metal elements except lithium is greater than or equal to 85%; The positive electrode active material includes secondary particles, the secondary particles include primary particles, the primary particles include slender primary particles, the particle size of each of the slender primary particles includes a longest diameter P1 and a shortest diameter P2, 1.5≤P1 / P2≤10, 0.1μm<P1≤3.5μm, 0.1μm≤P2≤0.6μm; the slender primary particles are arranged radially.
2. The lithium-ion battery according to claim 1, characterized in that Based on the total number of the primary particles in a single secondary particle, the number of the elongated primary particles accounts for 60% to 85%.
3. The lithium ion battery according to claim 1 or 2, characterized in that: Based on the total number of the primary particles in a single secondary particle, the number of the elongated primary particles accounts for 70% to 85%.
4. The lithium ion battery according to any one of claims 1 to 3, characterized in that: In a cross-sectional scanning electron microscope image of the secondary particle passing through the geometric center of the particle, the cross-section of a single secondary particle includes N1 primary particles; 250≤N1≤450.
5. The lithium ion battery according to any one of claims 1 to 4, characterized in that: The secondary particles are spherical in shape.
6. The lithium ion battery according to any one of claims 1 to 5, characterized in that: The volume median particle size Dv50 of the secondary particles is 8.5 μm to 12 μm.
7. The lithium ion battery according to any one of claims 1 to 6, characterized in that: The positive electrode active material includes a structural formula of Li a Ni b Co c Mn d M1 e O f material, wherein the M1 element includes one or more of Na, Mg, Zr, Al, Ca, W, Nb, Ta, Sr, K, Sb, Mo, W, 0.5≤a≤1.2, 0.85≤b≤0.99, 0<c≤0.1, 0<d≤0.05, 1.9≤f≤2.2, b+c+d+e=1.
8. The lithium ion battery according to any one of claims 1 to 7, characterized in that: A first coating layer is formed on the surface of the positive electrode active material. The first coating layer includes a first element. The first element includes one or more of Co, Al, F, and Ti.
9. The lithium-ion battery according to claim 8, characterized in that: Based on the molar amount of the positive electrode active material, the content of Co is 7000ppm to 15000ppm; and / or Based on the molar amount of the positive electrode active material, the content of Al is 300ppm to 1000ppm; and / or Based on the molar amount of the positive electrode active material, the content of F is 0 to 750 ppm; and / or The content of Ti is 300 ppm to 1000 ppm based on the molar amount of the positive electrode active material.
10. The lithium ion battery according to any one of claims 1 to 9, characterized in that: A second coating layer is formed on the surface of the positive electrode active material. The second coating layer includes a second element. The second element includes one or more of B, Al, and Y.
11. The lithium ion battery according to claim 10, characterized in that: The content of the second element is 500 ppm to 3000 ppm based on the molar amount of the positive electrode active material.
12. A positive electrode active material, characterized in that: The positive electrode active material comprises lithium nickel cobalt manganese oxide, and the molar proportion of nickel in other metal elements except lithium is greater than or equal to 85%; The positive electrode active material includes secondary particles, the secondary particles include primary particles, the primary particles include slender primary particles, the particle size of each of the slender primary particles includes a longest diameter P1 and a shortest diameter P2, 1.5≤P1 / P2≤10, 0.1μm<P1≤3.5μm, 0.1μm≤P2≤0.6μm; the slender primary particles are arranged radially.
13. The positive electrode active material according to claim 12, characterized in that: Based on the total number of the primary particles in a single secondary particle, the number of the elongated primary particles accounts for 60% to 85%.
14. An electrical device, characterized in that: The invention comprises the lithium ion battery according to any one of claims 1 to 11 and / or the positive electrode active material according to any one of claims 12 to 13.
Citation Information
Patent Citations
Pressure-resistant positive electrode active material and electrochemical energy storage device
CN111384371A
Positive electrode active material, positive electrode plate and lithium ion secondary battery
CN112447967A
Positive electrode active material, positive electrode plate, lithium ion battery and application thereof
CN115995531A
Electrode material and preparation method therefor, and electrode material precursor and preparation method therefor
WO2024067407A1
Cited By
Polycrystalline positive electrode material for sulfide all-solid-state battery, preparation method and secondary battery
CN120727805A